An Image Processing Method to Convert RGB Image into Binary - Ratri Dwi Atmaja; Muhammad Ary Murti; Junartho Halomoan; Fiky Yosef Suratman (Institute of Advanced Engineering and Science, 2016)
It is important in image processing to extract objects from their background into binary image. Binary image is used as input to feature extraction process and have an important role in generating unique feature to distinguish several classes in pattern recognition. This paper propose an image processing algorithm to obtain a binary image from RGB. The results showed that the binary image of the proposed algorithm contained the desired object.